PENDEKATAN BARU PEMETAAN BATHIMETRIC MENGGUNAKAN DATA PENGINDERAAN JAUH SPOT STUDI KASUS: TELUK PERIGI DAN TELUK POPOH (THE NEW APPROACH TO MAPPING BATHIMETRIC USING SPOT REMOTE SENSING DATA CASE STUDY: THE BAY AND POPOH GULF) - Arief, Muchlisin (Indonesian Journal of Aerospace, 2012)
Bathymetric mapping derived from remote sensing have been carried out researchers, in order to determine the depth of the shallow waters especially sallow water depth. Bathymetric relief map shows the earth/terrain depicted by contour lines is called the isobath. Usually bathymetric determination using exponential function of depth. While in this paper described a new approach to calculate the depth of seawater derived from SPOT-4 satellite data using empirical formulas functions of logarithmic or quadratic equation built through correlasi the depth map obtained from DIHIDROS (Navy) with Digital Number or the reflectance values of SPOT band-1. This experience has been tested at Perigi bay in Trenggalek district and Popoh bay in Tulung Agung district. Based on the calculations, the spread of sallow water depth on Perigi and popoh bay about 5 – 70 meters.